A Theoretical Explanation of Sport Trademark Litigation: Already v. Nike and Forever 21 v. Adidas. Issue 1 (2nd January 2023) - Cho, Sungho; Brison, Natasha; Brown, Katie; Quinn, Kevin
Abstract: Trademark law provides owners of legally protected marks with a set of legal claims against unauthorized users. Law and economics and brand equity theories rationalize the system of trademarks. Meanwhile, game theory explains why trademark rights must be legally protected and how parties in sport trademark litigation make decisions in anticipation of the opponents' expected course of action. Four game settings rationalize the utility of trademarks and showcase parties' strategic moves in trademark litigation: (1) prisoners' dilemma, (2) game of chicken, (3) sequential game, and (4) game of brinkmanship. Focusing on the Already v. Nike and Forever 21 v. Adidas trademark litigation cases, this study explores the interactive dynamics between parties and the factors associated with the parties' decision-making during the process of litigation.